Evaluation of Diuretic Activity of Aqueous Extract of Ripe Fruit Pulp of Tamarindus indica L. in Rats - Kaundinnyayana, Sammodavardhana; Mahadevaiahcandraiah, Satish Kumar; Udupa, Alaya Laxminarayana (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Diuresis is an important pharmacological property which is useful in many clinical conditions. There is a need of better diuretics with lesser adverse effects in comparison to currently available diuretics. The study aimed to evaluate the diuretic activity of aqueous extract of fruit pulp of Tamarindus indica L. in rats. Methods: The study was undertaken with aqueous extract of fruit pulp of Tamarindus indica in three doses: 300 mg/kg, 600 mg/kg and1200 mg/kg for its diuretic activity in comparison with standard (furosemide) and vehicle control (normal saline) in Wistar rats. Urine volume and electrolytes were measured after 24 hours of drug administration. Results: Aqueous extract of fruit pulp of Tamarindus indica at the dose of 1200 mg/kg exhibited significant diuretic activity (p<0.05) without significant natriuretic effect. Magnesium excretion was also significantly increased in comparison to control group. Conclusion: Aqueous extract of fruit pulp of Tamarindus indica has significant diuretic activity in Wistar rats.